Application of the Project Citizen Learning Model in Developing Social Intelligence Elementary School Students in Grade 5 and 6: Penerapan Model Pembelajaran Project Citizen Dalam Mengembangkan Kecerdasan Sosial Siswa Kelas 5 Dan 6 SD - Nurul Hulaimi Zamaluddin Lubis; Nur Maslikhatun Nisak (Academia Open, 2021)
The purpose of this study was to analyze the application of the Project Citizen Learning Model and social intelligence to the 5th and 6th graders of SD Muhammadiyah 01 Sidoarjo. The method used is descriptive qualitative. The result is that the steps in this model have been implemented by the teacher. Starting from the beginning of learning, teachers and students identify problems and seek information about public policies that exist in the community by discussing, groups will present their work and portfolios that have been made, reflecting on the learning experience at the end of the lesson. Based on the results of the questionnaire data obtained 89% of students are confident in making new friends, 97.8%. Students easily communicate with friends, 93.5% are able to communicate with other people including school workers, 79.7% help friends complete assignments, 90% are able to do school assignments well, 100% of students answer the mandate to take care of safekeeping items. With this Learning Model, not only cognitive abilities are obtained by students but the development of students' social intelligence is evident from the results of questionnaires distributed by researchers.